Higher Art Studies: Analysis of its legislative development and current situation - Moreno Bonilla, Mª Dolores (Avances en Supervisión Educativa, 2022)
The educational reforms of the last decades have opted to leave Higher Artistic Education outside the University, placing them in a dysfunctional space due to the absence of regulatory regulations according to the higher educational section that it develops. This article aims to make visible the anomalous situation experienced by these teachings and to publicize the solution proposals that are generated from the involved sectors. For this, the educational regulations and the pertinent literature related to the study of the situation, its assessment and improvement measures have been reviewed. In the conclusion, it is focused on the affiliation to the university, as a solution measure for the irregular situation that affects the higher art education.
Keywords: art education; higher art education; university; European Higher Education Area; academic organization; educational legislation